2012
DOI: 10.4236/ojn.2012.23024
|View full text |Cite
|
Sign up to set email alerts
|

Healthy lifestyle for people with intellectual disabilities through a health intervention program

Abstract: There are well known gaps related to health care service and public health interventions for people with Intellectual Disabilities (ID), but there is still lack of research information of what nurses can do to reducing health disparities of persons with ID. The present study aimed at exploring the views of people with ID about a healthy lifestyle, exercise, and to take part in a health promotion program. A qualitative method was an appropriate method for capturing the informants' points of view. Participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…Particularly with regard to the attribute of ‘health education’, the relevant studies found that the interventions had a positive impact on people with ID and made them feel more empowered. Training people with ID in health rights , providing adults with ID with a diary to assess their own health , developing health‐related educational material about health promotion with respect to health literacy and listening to individuals’ perspectives on health were the most important alternative health‐promotion strategies that contributed to empowering people with ID.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly with regard to the attribute of ‘health education’, the relevant studies found that the interventions had a positive impact on people with ID and made them feel more empowered. Training people with ID in health rights , providing adults with ID with a diary to assess their own health , developing health‐related educational material about health promotion with respect to health literacy and listening to individuals’ perspectives on health were the most important alternative health‐promotion strategies that contributed to empowering people with ID.…”
Section: Resultsmentioning
confidence: 99%
“…Physical fitness and regular physical activity are key factors in health and wellbeing of all individu als, including those with an intellectual disability (ID) (Lorentzen & Wikström, 2012). Physical fitness in most definitions includes the following compo nents: body composition, cardiorespiratory capacity, muscle strength and endurance, balance and flexibi lity.…”
Section: Introductionmentioning
confidence: 99%
“…Living independently/with family (78%) or in a community group home (74%) were the most frequently cited living arrangement related to excess weight. Moreover, the level of ID was significantly associated with a BMI ≥ 25, with mild or moderate ID posing Further challenges equating feelings of hunger and satiety to food consumption may also act as contributory factors (Rubbert 2012) signifying support to maintain a healthy lifestyle (Lorentzen & Wikström 2012).…”
Section: Discussionmentioning
confidence: 99%